Respiratory and Otolaryngology Symptoms Following the 2019 Spring Floods in Quebec - Landaverde, Elsa; Généreux, Mélissa; Maltais, Danielle; Gachon, Philippe (International Journal of Environmental Research and Public Health, 2022)
Background: Although floods may have important respiratory health impacts, few studies have examined this issue. This study aims to document the long-term impacts of the spring floods of 2019 in Quebec by (1) describing the population affected by the floods; (2) assessing the impacts on the respiratory system according to levels of exposure; and (3) determining the association between stressors and respiratory health. Methods: A population health survey was carried out across the six most affected regions 8–10 months post-floods. Data were collected on self-reported otolaryngology (ENT) and respiratory symptoms, along with primary and secondary stressors. Three levels of exposure were examined: flooded, disrupted and unaffected. Results: One in ten respondents declared being flooded and 31.4% being disrupted by the floods. Flooded and disrupted participants reported significantly more ENT symptoms (adjusted odds ratio (aOR): 3.18; 95% CI: 2.45–4.14; aOR: 1.76; 95% CI: 1.45–2.14) and respiratory symptoms (aOR: 3.41; 95% CI: 2.45–4.75; aOR: 1.45; 95% CI: 1.10–1.91) than the unaffected participants. All primary stressors and certain secondary stressors assessed were significantly associated with both ENT and respiratory symptoms, but no “dose–response” gradient could be observed. Conclusion: This study highlights the long-term adverse effects of flood exposure on respiratory health.
Number: 18 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Gachon_Philippe; Généreux_Mélissa; Infolettre; Infolettre_Octobre_2022; Site_internet_RIISQ

Pour une défense collective face à la fatigue pandémique: L’urgence de renforcer les facteurs protecteurs - Généreux, Mélissa; Blouin-Genest, Gabriel; Landaverde, Elsa; Torres Orozco, Et Natalia (Global Health Promotion, 2024)
Résumé: De nombreux articles publiés récemment ont laissé apparaître l’émergence d’un nouveau phénomène dans notre rapport avec la pandémie de COVID-19 : la fatigue pandémique. Ce phénomène suggère l’apparition d’une tendance générale de lassitude face aux mesures sanitaires et à l’état d’urgence devenu permanent. L’objectif de cet article est de replacer cet enjeu dans le contexte de la réalisation d’un projet de recherche portant sur les impacts psychosociaux durant la pandémie. Si relativement peu de recherches se sont intéressées à la fatigue pandémique, la réalité de ce phénomène a été mise en évidence dans le cadre d’un projet de recherche multi-annuelle effectuée durant la pandémie. En termes de méthode, notre équipe multidisciplinaire à l’Université de Sherbrooke a développé un protocole d’enquête permettant d’évaluer les effets de la pandémie de COVID-19 sur la santé mentale à travers des études transversales répétées. La dernière phase de l’enquête inclut un volet additionnel qui cherche à comprendre de quelle manière les conséquences de la pandémie peuvent s’appliquer à d’autres crises systémiques, notamment aux changements climatiques. Différentes vagues d'enquêtes nationales et internationales ont ainsi été réalisées (8 pays, taille minimale de l’échantillon 1000–1500 et échantillonnage par quota mis en oeuvre adapté à chaque pays et basé sur les données démographiques disponibles), et suivant l’évolution de la pandémie, nous avons introduit la notion de fatigue pandémique, ainsi que de fatigue climatique, afin de pouvoir mesurer l’impact de l’exposition prolongée à ces crises mondiales. Ces nouvelles données confirment nos résultats originaux : l’impact psychosocial de la pandémie est immense, en particulier en termes de fatigue pandémique, phénomène qui se retrouve à la fois au niveau comportemental et informationnel. Cette fatigue est un indicateur important à considérer afin d’améliorer notre capacité de réaction et d’adaptation à cette crise, mais également à celles futures.
Keywords: Généreux_Mélissa

Intersectoral research and multi-risk approaches in Québec: systemic risk management and its psychosocial consequences - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Contribution paper to the Global Assessment Report on Disaster Risk Reduction, 2022)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Lessard_Lily; Site_internet_RIISQ

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ